Hematological indices in prolonged menstruation: New roles for blood groups and coagulation factors - Shahbazi, Shirin (Archives of Medical Laboratory Sciences, 2020)
Background: Menorrhagia is the most common type of abnormal uterine bleeding, caused by disruption of hormonal regulation, uterine function or blood clotting. Developing an effective diagnostic strategy will improve patient’s quality of life and management. Here we investigated the links between hematological characteristics and prolonged menstruation‎ to estimate the importance of the first line coagulation screening tests in young women ‎. Materials and Methods: In a case-control design and under supervision of a specialist, 43 cases and 104 age matched controls were selected. Menstrual characteristics were evaluated by a standardized questionnaire distributed to high school and university young students. Hematological indices including first line coagulation screening tests were performed for both groups and statistically assessed. Result: Statistical analysis showed that prolonged menstrual bleeding ‎is significantly correlated to prolonged bleeding time (p value, 0.01) as well as ‏ red blood cell count (p value, 0.04). The O blood group showed the greatest contribution to the bleeding periods longer than 7 days (53.4 %(. Additional coagulation tests revealed one coagulation factor VII deficiency patient. Conclusion: The results of the present study revealed the importance of menorrhagia management in young women and showed a significant correlation between prolonged menstrual bleeding ‎and blood types ‎. Our study findings also suggest a significant association between prolonged menstruation and bleeding time test, emphasizing on the role of blood coagulation traits in susceptibility to heavy menstrual bleeding.